Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1039856220975286
|View full text |Cite
|
Sign up to set email alerts
|

The uncertainty trope: the duty to treat during a pandemic

Abstract: Background: Past guidance in the codes of practice urged doctors to provide treatment even in the context of extreme adversities. Despite the significant societal changes of recent times, contemporary guidance regarding the duty to treat during a pandemic has been limited. Objective: The authors herewith examine deontological aspects pertaining to the duty to treat during a pandemic and the potential disruptions to health care services. Conclusion: The ethical, legal and professional guidance for duty of care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Healthcare workers (HCWs) at the forefront of providing aid during pandemic outbreaks are exposed to risk, facing demanding professional responsibilities 1 and uncertainties concerning their principal duty to care. 2 Especially in times of crisis, and when there is a perceived high risk of infection, ethical concerns are visible in the case of public healthcare sectors. Previous studies have reported the following concerns among healthcare professionals during pandemics: fear of infection, 3 perceived risk, 4 , 5 concerns regarding work conditions, 6 perceived stigma, 7 , 8 low emotional well-being 9 and psychosocial distress.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HCWs) at the forefront of providing aid during pandemic outbreaks are exposed to risk, facing demanding professional responsibilities 1 and uncertainties concerning their principal duty to care. 2 Especially in times of crisis, and when there is a perceived high risk of infection, ethical concerns are visible in the case of public healthcare sectors. Previous studies have reported the following concerns among healthcare professionals during pandemics: fear of infection, 3 perceived risk, 4 , 5 concerns regarding work conditions, 6 perceived stigma, 7 , 8 low emotional well-being 9 and psychosocial distress.…”
Section: Introductionmentioning
confidence: 99%